Apolipoprotein C-II: the re-emergence of a forgotten factor. Issue 3 (June 2020) - Wolska, Anna; Reimund, Mart; Remaley, Alan T.
Abstract : Purpose of review: Apolipoprotein C-II (apoC-II) is a critical cofactor for the activation of lipoprotein lipase (LPL), a plasma enzyme that hydrolyzes triglycerides (TG) on TG-rich lipoproteins (TRL). Although apoC-II was first discovered nearly 50 years ago, there is renewed interest in it because of the recent efforts to develop new drugs for the treatment of hypertriglyceridemia (HTG). The main topic of this review will be the development of apoC-II mimetic peptides as a possible new therapy for cardiovascular disease. Recent findings: We first describe the biochemistry of apoC-II and its role in TRL metabolism. We then review the clinical findings of HTG, particularly those related to apoC-II deficiency, and how TG metabolism relates to the development of atherosclerosis. We next summarize the current efforts to develop new drugs for HTG. Finally, we describe recent efforts to make small synthetic apoC-II mimetic peptides for activation of LPL and how these peptides unexpectedly have other mechanisms of action mostly related to the antagonism of the TG-raising effects of apoC-III. Summary: The role of apoC-II in TG metabolism is reviewed, as well as recent efforts to develop apoC-II mimetic peptides into a novel therapy for HTG.